The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/jct.2014.51009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Tumour Suppressor Function of DOK7 in Human Breast Cancer

Abstract: Introduction: Downstream of tyrosine kinase 7 (DOK-7) is a member of the DOK family, which has been associated with the development and progression of various humancancers. Previously, identification of CpG hypermethylation in DOK-7 promoter was identified in breast cancer. Method: DOK-7 mRNA extraction and reverse transcription were performed on fresh frozen breast cancer tissue samples and normal background breast tissue. Transcript levels of expression were analyzed against TNM stage, tumour grade and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Several studies suggested DOK7 as a potential tumor-suppressor gene, because of the significantly low expression levels in BC tissues compared with normal tissues. The lower expression level of DOK7 was associated with the greater aggressive clinical behaviors and poorer prognosis in BC 47 . The mechanistic studies by Yue et al 48 illustrated that DOK7 inhibited proliferation and invasion of BC cells through PI3K/PTEN/AKT pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies suggested DOK7 as a potential tumor-suppressor gene, because of the significantly low expression levels in BC tissues compared with normal tissues. The lower expression level of DOK7 was associated with the greater aggressive clinical behaviors and poorer prognosis in BC 47 . The mechanistic studies by Yue et al 48 illustrated that DOK7 inhibited proliferation and invasion of BC cells through PI3K/PTEN/AKT pathway.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies suggested DOK7 as a potential tumor-suppressor gene, because of the signi cantly low expression levels in BC tissues compared with normal tissues. The lower expression level of DOK7 was associated with the greater aggressive clinical behaviors and poorer prognosis in BC [45]. The mechanistic studies by Yue et al illustrated that DOK7 inhibited proliferation and invasion of BC cells through PI3K/PTEN/AKT pathway [46].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of identical twins with differential breast cancer statuses identified DOK7 gene methylation as an indicator of breast cancer risk [ 20 ]. Increased expression of DOK7 has been correlated with longer patient survival time, and decreased expression of the gene has been seen in patients with recurrent cancers [ 21 ]. To our knowledge, a role of DOK7 in tamoxifen resistance has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%